Folding of the HDV antigenomic ribozyme pseudoknot structure deduced from long-range photocrosslinks. - Bravo, C (1996)
A trans-acting system has been designed in order to explore the three-dimensional structure of the anti-genomic HDV ribozyme. In this system, the substrate (SANT) is associated by base-pairing to the catalytic RNA (RzANT) forming helix H1. RzANT is able to cleave specifically the RNA substrate as well as a deoxysubstrate analogue containing a single ribocytidine at the cleavage site (position -1). This demonstrates that such deoxysubstrate analogues are valuable tools for structural studies of this ribozyme domain. They form however weak complexes with RzANT which is due in part to their ability to fold as stable hairpins unlike the RNA substrate. Using a set of full deoxy or of mixed deoxy-ribo substrate analogues site-specific substituted with the photoaffinity probe deoxy-4-thiouridine, ds4U, at a defined position, we were able to determine a number of long range contacts between the substrate and the ribozyme core. In particular, crosslinks between substrate position -1 and position -2 with residues C15, G19 and C67, thought to be involved in the ribozyme catalytic site, were detected. A three dimensional model of the antigenomic ribozyme system, derived from the structure proposed by Tanner et al. [Current Biol (1994) 4, 488-498] for the genomic system was constructed. Apart from residue deletion or insertion, only minor accommodations were needed to account for all photocrosslinks but one which is attributed to an alternative hybridization of the substrate with the ribozyme. This study therefore further supports the structure proposed by Tanner et al. for the pseudoknot model.